2019
DOI: 10.18632/aging.102113
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of lncRNA MALAT1 alleviates vascular lesion and vascular remodeling of rats with hypertension

Abstract: Objective: Recently, the effect of long non-coding RNAs (lncRNAs) in hypertension (HTN) has been identified. This study aims to explore the expression of lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in HTN and its role in vascular lesion and remodeling of HTN rats. Results: LncRNA MALAT1 expression was up-regulated in HTN patients, and lncRNA MALAT1 could be an effective index of HTN diagnosis. Down-regulated MALAT1 and inhibited Notch-1 could reduce relative factor express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…For example, LncRNA AK094457 was up‐regulated in hypertensive rats, and silencing AK094457 reduced arterial pressure of rats and inhibited Ang II‐induced vascular endothelial dysfunction 11 . LncRNA MALAT1 was up‐regulated in venous blood from HPT patients and vascular tissues of hypertensive rats, and silencing MALAT1 reduced vascular fibrosis and inhibited aortic EC apoptosis 12 . However, the studies focused on the regulation of LncRNAs in vascular EC injury in Ang II‐induced HPT still lack.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LncRNA AK094457 was up‐regulated in hypertensive rats, and silencing AK094457 reduced arterial pressure of rats and inhibited Ang II‐induced vascular endothelial dysfunction 11 . LncRNA MALAT1 was up‐regulated in venous blood from HPT patients and vascular tissues of hypertensive rats, and silencing MALAT1 reduced vascular fibrosis and inhibited aortic EC apoptosis 12 . However, the studies focused on the regulation of LncRNAs in vascular EC injury in Ang II‐induced HPT still lack.…”
Section: Introductionmentioning
confidence: 99%
“…13 Examination of the top ten up- and down-regulated genes in miR-181a/b-1 KO mice showed that most genes are cell-specifically regulated (Figure 6 and Table S2). Amongst the top up-regulated genes were Stat4 in B cells (fold change=11, expression validated by real-time PCR in Figure S6) which is associated with inflammation, 14 collagen genes associated with fibrosis such as Col4a1 (fold change=1.5) in endothelial cells, Cd81 a marker of renal-resident macrophages 15 (fold change=1.2), Flt3l found in natural killer cells (only expressed in miR-181a/b-1 KO mice) which exacerbates accumulation of T cells in the kidney, 16 Malat1 found in macrophages (fold change=1.2) shown to be higher in hypertensive patients and blockade of Malat1 was able to lower BP in an animal model, 17 Notch2 in proximal tubules (only expressed in miR- 181a/b-1 KO mice) which is involved in nephron development, 18 and Polr2f found in proximal tubules (fold change=2.2) previously associated with established hypertension in a meta-analysis. 19 Several of the up-regulated genes have been previously demonstrated to have a role in renal injury, inflammation and fibrosis including Cxcl16 20 found in distal convoluted tubule cells (fold change=2.1), and Smad4 found in collecting duct principal cells (fold change=1.3).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of MALAT1 expression rescued the rats’ cardiac function due to a restoration of the PI3K/AKT signaling pathway [ 148 ]. Studies in the rat model of hypertension showed that MALAT1 expression was increased in the heart [ 149 , 150 ]. Overexpression of MALAT1 caused severe cardiac fibrosis and remodeling by reducing the expression of MyoD that is responsible for the contractile phenotype of the heart [ 149 ].…”
Section: Long Non-coding Rnas In Cvdmentioning
confidence: 99%